2016
DOI: 10.1016/j.eurpsy.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Big Five personality traits and medically unexplained symptoms in later life

Abstract: Older patients with MUS have a specific personality profile, comparable to MES patients. Health anxiety and somatization may be better indicators of psychopathology than whether a physical symptom is medically explained or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Traditionally, high Agreeableness in adult lifespan is thought to be a positive trait of personality being associated with increased subjective well-being (39), better outcome in mental health treatments (40), less disengagement coping (41), and less sexual aggressive behavior (42). In old age, higher Agreeableness levels have been instead associated with poorer executive performance and neurocognitive functions (43)(44)(45) and medically unexplained symptoms (46). The role of higher levels of Conscientiousness in old age is equally ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, high Agreeableness in adult lifespan is thought to be a positive trait of personality being associated with increased subjective well-being (39), better outcome in mental health treatments (40), less disengagement coping (41), and less sexual aggressive behavior (42). In old age, higher Agreeableness levels have been instead associated with poorer executive performance and neurocognitive functions (43)(44)(45) and medically unexplained symptoms (46). The role of higher levels of Conscientiousness in old age is equally ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…From the largest study on comorbidity rates emerged that 50.6% of patients suffering from MUPS has a personality disorder. Other authors showed that MUPS are often associated to affective disorders, primarily depression, and especially in later life ( 24 , 25 ). The role of inflammation in major depressive disorder (MDD) and the impact of exposure to early stressful events in increasing the vulnerability to develop psychopathologies may represent a possible common ground in developing physical symptoms, involving similar underlying pathogenic mechanisms ( 26 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis states that one of the most clinically noticeable problems of the patient with somatization is personality dysfunction. The estimated comorbidity of somatization and personality malfunction varies from 48 to 72% [13].…”
Section: Introductionmentioning
confidence: 99%